Rest is resistance : a manifesto - Hersey, Tricia (Little, Brown Spark, 2022)
"Disrupt and push back against capitalism and white supremacy. In this book, Tricia Hersey, aka The Nap Bishop, encourages us to connect to the liberating power of rest, daydreaming, and naps as a foundation for healing and justice. What would it be like to live in a well-rested world? Far too many of us have claimed productivity as the cornerstone of success. Brainwashed by capitalism, we subject our bodies and minds to work at an unrealistic, damaging, and machine-level pace -- feeding into the same engine that enslaved millions into brutal labor for its own relentless benefit. In Rest Is Resistance, Tricia Hersey, aka the Nap Bishop, casts an illuminating light on our troubled relationship with rest and how to imagine and dream our way to a future where rest is exalted. Our worth does not reside in how much we produce, especially not for a system that exploits and dehumanizes us. Rest, in its simplest form, becomes an act of resistance and a reclaiming of power because it asserts our most basic humanity. We are enough. The systems cannot have us. Rest Is Resistance is rooted in spiritual energy and centered in Black liberation, womanism, somatics, and Afrofuturism. With captivating storytelling and practical advice, all delivered in Hersey's lyrical voice and informed by her deep experience in theology, activism, and performance art, Rest Is Resistance is a call to action, a battle cry, a field guide, and a manifesto for all of us who are sleep deprived, searching for justice, and longing to be liberated from the oppressive grip of Grind Culture"--provided by publisher.